Evaluation of egg parasitoid Hadronotus pennsylvanicus as a prospective biocontrol agent of the leaffooted bug Leptoglossus zonatus - Robert K. Straser; Kent M. Daane; Elijah Talamas; Houston Wilson (BioControl, 2022)
The western leaffooted bug, Leptoglossus zonatus (Dallas) (Heteroptera: Coreidae), is a key pest of almonds and pistachios in the USA. With limited monitoring strategies and no economic threshold developed, the use of broad-spectrum insecticides remains the primary control tactic for L. zonatus . In pursuit of more sustainable management options, experiments were carried out to assess the biocontrol potential of the egg parasitoid Hadronotus pennsylvanicus (Ashmead) (Hymenoptera: Scelionidae) against L. zonatus . Biological and demographical attributes of H. pennsylvanicus were evaluated under controlled laboratory conditions. Mated females lived on average 116 days. However, female longevity declined by 74% when provided with host eggs, and by 97% when deprived of a suitable diet. Females produced an average 39.70 offspring, with peak fecundity observed within the first week of their lifespan. The total progeny was on average 92.75% female. Non-reproductive host mortality accounted for > 52% of the total egg mortality observed within the first two weeks, and represented the majority of total host egg mortality thereafter. Age of host eggs did not influence parasitism rates. Under laboratory conditions, H. pennsylvanicus exhibits suitable demographic and reproductive traits as a candidate biocontrol agent of L. zonatus . Further research is needed to determine how to best manipulate and enhance H. pennsylvanicus populations to promote biocontrol of L. zonatus under field conditions.

Life-history and host preference of Trichopria drosophilae, a pupal parasitoid of spotted wing drosophila - Xin-Geng Wang; Gülay Kaçar; Antonio Biondi; Kent M. Daane (BioControl, 2016)

Classic biological control of olive fruit fly in California, USA: release and recovery of introduced parasitoids - Kent M. Daane; Xingeng Wang; Diego J. Nieto; Charles H. Pickett; Kim A. Hoelmer; Arnaud Blanchet; Marshall W. Johnson (BioControl, 2015)

Low temperature storage effects on two olive fruit fly parasitoids - Kent M. Daane; Xin-geng Wang; Marshall W. Johnson; Monica L. Cooper (BioControl, 2013)

Syrphid flies suppress lettuce aphids - Erik H. Nelson; Brian N. Hogg; Nicholas J. Mills; Kent M. Daane (BioControl, 2012)

Erratum to: Establishment of Psyllaephagus parvus and P. perplexus as serendipitous biological control agents of Eucalyptus psyllids in southern California - Michele Eatough Jones; Kent M. Daane; Timothy D. Paine (BioControl, 2011)

Establishment of Psyllaephagus parvus and P. perplexans as serendipitous biological control agents of Eucalyptus psyllids in southern California - Michele Eatough Jones; Kent M. Daane; Timothy D. Paine (BioControl, 2011)

Comparative evaluation of two olive fruit fly parasitoids under varying abiotic conditions - Xin-geng Wang; Marshall W. Johnson; Victoria Y. Yokoyama; Charles H. Pickett; Kent M. Daane (BioControl, 2011)

The biology of Bracon celer as a parasitoid of the olive fruit fly - Karen R. Sime; Kent M. Daane; John W. Andrews; Kim Hoelmer; Charles H. Pickett; Hannah Nadel; Marshall W. Johnson; Russell H. Messing (BioControl, 2006)